2017
DOI: 10.2147/bctt.s126557
|View full text |Cite
|
Sign up to set email alerts
|

<em>CYP2D6</em> polymorphisms may predict occurrence of adverse effects to tamoxifen: a preliminary retrospective study

Abstract: Introduction and aimsTamoxifen is an adjuvant drug effective in treating hormone receptor – positive breast cancer. However, 30%–50% of patients relapse and many develop adverse effects, such as hot flashes and fatty liver. Allelic variations altering the activity of cytochrome P450-2D6 enzyme affect response to tamoxifen by modulating metabolism of tamoxifen into its pharmacologically active metabolite endoxifen. Although association between CYP2D6 polymorphisms and recurrence of breast cancer in patients on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…( p = 0.06) • Hazard ratios of developing hot flashes/night sweats: o PM vs EM: 1.94 (95% CI: 1.12–3.35) o IM vs EM: 1.16 (95% CI: 0.81–1.64) Ruddy et al, 2013 [ 36 ]; USA Oncology centre at a local cancer institute Stage I-III breast cancer patients undergoing tamoxifen therapy ( N = 99) CYP2D6 • CYP2D6 metabolic activity classes (including a rare allele (RA) class – individuals in this class have an EM phenotype) • Occurrence of hot flashes • Level of bother caused by hot flashes • Questionnaire developed based on the Breast Cancer Prevention Trial scale of menopausal symptoms Comparison between CYP2D6 metabolic activity classes • The proportion of patients having developed hot flashes is similar between the UM/EM/RA group and IM group. (67% vs 69%) • The proportion of patients expressing that they are at least slightly bothered by hot flashes is similar between the UM/EM/RA group and IM group (63% vs 69%) • The proportion of patients expressing that they are at least moderately bothered by hot flashes is similar between the UM/EM/RA group and IM group (34% vs 38%) Wickramage et al, 2017 [ 37 ]; Sri Lanka Hospital clinic at the National Cancer Institute in Sri Lanka Breast cancer patients undergoing tamoxifen treatment ( N = 24) CYP2D6 • SNPs of CYP2D6 • Occurrence of hot flashes • Occurrence of hot flashes reported in clinical records The CYP2D6*4 SNP (1846 G > A) • The existence of the CYP2D6*4 SNP in patients was not associated with the occurrence of hot flashes among them ( p = 0.437) The CYP2D6*41 SNP (Combination of 2988 G > A, 2850 C > T and -1584C) • The existence of the CYP2D6*41 SNP in patients was not associated with the occurrence of hot flashes among them ( p = 0.271) Zembutsu et al, 2017 [ 38 ]; Japan and Singapore Multi-sites; Hospitals, cancer centres and cancer institutes in Japan and Singapore Oestrogen receptor -positive, human epidermal growth factor receptor 2-negative, invasive breast cancer patients undergoing tamoxifen therapy ( N = 279) CYP2D6 • SNPs/Genotypes of CYP2D6 • Occurrence of hot flashes • Not specified • There was no significant difference in hot flashes occurrence between patients bearing the wt CYP2D6 and those having the CYP2D6 SNPs/genotypes investigated in this study ( p = 0.25) Abbreviation : CYP cytochrome P450, EM extensive metaboliser, IM intermediate metaboliser, PM poor metaboliser, RA rare allele, SNP single nucleotide poly...…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…( p = 0.06) • Hazard ratios of developing hot flashes/night sweats: o PM vs EM: 1.94 (95% CI: 1.12–3.35) o IM vs EM: 1.16 (95% CI: 0.81–1.64) Ruddy et al, 2013 [ 36 ]; USA Oncology centre at a local cancer institute Stage I-III breast cancer patients undergoing tamoxifen therapy ( N = 99) CYP2D6 • CYP2D6 metabolic activity classes (including a rare allele (RA) class – individuals in this class have an EM phenotype) • Occurrence of hot flashes • Level of bother caused by hot flashes • Questionnaire developed based on the Breast Cancer Prevention Trial scale of menopausal symptoms Comparison between CYP2D6 metabolic activity classes • The proportion of patients having developed hot flashes is similar between the UM/EM/RA group and IM group. (67% vs 69%) • The proportion of patients expressing that they are at least slightly bothered by hot flashes is similar between the UM/EM/RA group and IM group (63% vs 69%) • The proportion of patients expressing that they are at least moderately bothered by hot flashes is similar between the UM/EM/RA group and IM group (34% vs 38%) Wickramage et al, 2017 [ 37 ]; Sri Lanka Hospital clinic at the National Cancer Institute in Sri Lanka Breast cancer patients undergoing tamoxifen treatment ( N = 24) CYP2D6 • SNPs of CYP2D6 • Occurrence of hot flashes • Occurrence of hot flashes reported in clinical records The CYP2D6*4 SNP (1846 G > A) • The existence of the CYP2D6*4 SNP in patients was not associated with the occurrence of hot flashes among them ( p = 0.437) The CYP2D6*41 SNP (Combination of 2988 G > A, 2850 C > T and -1584C) • The existence of the CYP2D6*41 SNP in patients was not associated with the occurrence of hot flashes among them ( p = 0.271) Zembutsu et al, 2017 [ 38 ]; Japan and Singapore Multi-sites; Hospitals, cancer centres and cancer institutes in Japan and Singapore Oestrogen receptor -positive, human epidermal growth factor receptor 2-negative, invasive breast cancer patients undergoing tamoxifen therapy ( N = 279) CYP2D6 • SNPs/Genotypes of CYP2D6 • Occurrence of hot flashes • Not specified • There was no significant difference in hot flashes occurrence between patients bearing the wt CYP2D6 and those having the CYP2D6 SNPs/genotypes investigated in this study ( p = 0.25) Abbreviation : CYP cytochrome P450, EM extensive metaboliser, IM intermediate metaboliser, PM poor metaboliser, RA rare allele, SNP single nucleotide poly...…”
Section: Resultsmentioning
confidence: 98%
“…The publication year ranges between 2005 and 2018. The single-country studies were conducted in Australia [28], Canada [26,32], the Czech Republic [25], the Netherlands [27,31], Sri Lanka [37] or the United States [29,30,33,36]. Three further studies involved an international collaboration of research groups [34,35,38].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…However, about 30%-50% of those patients may develop relapse. Previous studies provided evidence that allelic variations in cytochrome P450-2D6 enzyme highly affect response to tamoxifen by modulating the metabolism of tamoxifen into its pharmacologically active metabolite endoxifen (Wickramage et al, 2017). Although CYP2D6 polymorphisms has been investigated in many studies in the western countries, the results of its role on tamoxifen concentrations as well as its impact on the clinical outcomes of the treated patients are conflicting and still not clear (Markopoulos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A recent article reported that functional CYP2D6 single-nucleotide polymorphisms (SNPs) were significantly associated with adverse effect fatty liver following the tamoxifen therapy. Therefore, alternative treatment can be used for patients with CYP2D6 SNPs (rs28371725 and rs16947) [18].…”
Section: Discussionmentioning
confidence: 99%